PEMIKIRAN FILSAFAT POLITIK ABDOLKARIM SOROUSH - Adi Bunardi (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2021)
The ideas of freedom, justice, democracy and secularism are the main themes in the study of political philosophy. This article attempts to explain Abdolkarim Soroush's political philosophy with the boundaries of themes regarding freedom, justice, secluralism and democracy. Abolkarim Soroush is a thinker in the contemporary Islamic world.